“BISAKAH KASUS MARIO-RUBICON ‘HANCURKAN’ KEPERCAYAAN PADA PAJAK?”: ANALISIS WACANA KRITIS PENDEKATAN TEUN A. VAN DIJK DALAM PEMBERITAAN CNN INDONESIA - Anggreini Riana Pasa; Fania Nurtriana; Lami Karyani Dicsi Sidauruk; Lasenna Siallaga; Septiana Pradyta; Agnes Endwitri Sihombing (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
This study aims to determine the macro and micro structures as well as cognition and social context in the news coverage of "Could the Mario-Rubicon Case 'Destroy' Trust in Taxes?" in CNN Indonesia by using the critical discourse analysis approach of Teun A van Dijk. The method used is descriptive qualitative method, namely research that aims to present a complete picture of social conditions. In other words, this research aims to investigate and clarify a phenomenon or social reality. Data sources in this study are divided into primary and secondary data sources. The primary data source was obtained from an online news article entitled “Could the Mario-Rubicon Case 'Break' Trust in Taxes?” from CNN Indonesia, while secondary data sources are in the form of journal articles, book references, and other relevant documents and supports. The stages of data analysis in this study started from suspicion, classification, and data interpretation. Based on the research results, the macro structure in the news is the alleged case of showing off assets in the form of a Rubicon which was committed by Mario Dandy Satrio as the son of the Head of the General Section of the DGT Ministry of Finance South Jakarta Regional Office II which will impact public trust in paying taxes. In the microstructure there are elements, including coherence (including additive coherence, conditional coherence, differentiating coherence), denial, sentence form, pronouns, setting, detail, intent, lexicon, and graphics. The social context in the news is shown through the economic recovery after the start of the easing of Covid-19 so that matters related to finance and taxes become more sensitive among the public.